Direct shear behavior of precast panel connections with cast-in-place shear keys using steel fiber-reinforced cementitious mortar (SFRCM). (August 2021) - Park, Sang-Hyun; Dinh, Ngoc Hieu; Kim, Seung-Hee; Lee, Seung-Jae; Choi, Kyoung-Kyu
Abstract: In the present study, an experimental study was performed to investigate the direct shear behavior of precast panel connections using steel fiber-reinforced cementitious mortar shear keys. The main experimental parameters included the volume fraction of steel fibers adopted for the connections and the details and configurations of the cast-in-place shear keys. The volume fractions of steel fibers were in the range of 0.75–1.5%. In total, four series with 22 push-off test specimens were fabricated and tested with various shear key configurations. The experimental results obtained were analyzed and discussed in detail to examine the effects of various parameters on the shear behavior of the panel connections. On the basis of the experimental results and theoretical shear transfer mechanism, an analytical model to predict the shear strength of the panel connections with shear keys was proposed, and its predictions showed a good correlation with the experimental results.